Avaliação da atividade e mecanismo de ação gastroprotetor do extrato hidroetanólico das folhas de Terminalia argentea Mart. - Beserra, Angela Márcia Selhorst e Silva (2018)
Popularly known as capitão, Terminalia argentea (Combretaceae) is a plant native to Brazil, whose infusion of leaves is used for ulcers. This work was carried out to investigate the toxicity and to evaluate the antiulcer activity and mechanism of the hydroethanolic extract of the leaves of T. argentea (HETa) in in vivo and in vitro models, as well as to advance in the phytochemical analyzes. The preliminary phytochemistry and TLC of HETa revealed the presence of phenolic compounds, flavonoids, saponins, tannins and phytosterols. The CLAE data revealed the presence of gallic acid, rutin, ellagic acid, catechin, quercetin and kaempferol. In the mass spectrometry analysis, the presence of gallic acid, rutin, ellagic acid and quercetin were confirmed and others also identified. Phenols, total flavonoids and phytosterols obtained by spectrophotometry represented 18.8, 10.8 and 18.9% of lyophilized extract composition, respectively. In the Alamar blue assay, HETa showed no cytotoxic effect on CHO-K1 and AGS cell lines. In vitro genotoxicity of HETa (10, 30 or 100 μg/mL) was assessed by micronucleus and comet assays using CHO-K1 cells. In the micronucleus assay HETa increased the micronucleus and nuclear bud number in binucleate cells at the three concentrations tested and the nucleoplasmic bridge number at 30 μg/mL. In the comet test, HETa (10 and 100 μg/mL) was genotoxic in CHO-K1 cells not exposed to H2O2. In the pretreatment, HETa at all concentrations tested prevented DNA damage induced by H2O2 exposure. In co-treatment with H2O2, HETa was genotoxic at all three concentrations. And in the post-treatment, DNA damage in CHO-K1 cells exposed to H2O2 was reversed in 22.5% with 10 μg/mL HETa. In the acute toxicity test HETa given in a single dose of up to 2000 mg/kg did not cause death in the mice, and the clinical signs that emerged were reversible piloerection and diarrhea. No macroscopic changes were observed in the analyzed organs. The subchronic toxicity test was performed by oral administration of HETa (50, 200 and 800 mg/kg) in rats for 30 days. Feed intake in the group treated with 800 mg/kg was lower on the 18th day. Subchronic administration of HETa also reduced total cholesterol by 13% in animals treated with 800 mg/kg and basophilia was observed at the dose of 50 mg/kg. No other alteration was observed in the other biochemical and hematological parameters in the three doses tested. There were no macroscopic and histopathological changes in the organs of animals treated with HETa, but the relative heart weight of animals treated with 800 mg/kg was 13.2% lower than in the vehicle group. The gastroprotective activity and the antisecretory effect of HETa (12.5, 50 and 200 mg/kg) were evaluated in mice ulcerated by ethanol/HCl and pylorus ligation, respectively. HETa (12.5 and 50 mg/kg) decreased by 55.8 and 40.6%, and carbenoxolone (100 mg/kg v.o) by 47.9% the gastric lesions induced by ethanol/HCl. In mice with pylorus ligation, HETa reduced gastric volume by 78.4, 36.1 and 43.7% at the doses 12.5, 50 and 200 mg/kg, respectively, and omeprazole by 30.9%. HETa also reduced total acidity by 85.8% (50 mg / kg) and 45.8% (200 mg / kg), while omeprazole reduced by 58.3%. In the pH analysis, the administration of HETa increased pH at the doses of 50 (68.4%) and 200 mg/kg (56.3%), and omeprazole by 86.3%. In the DPPH, FRAP and NO assays, the HETa showed antioxidant effect in vitro with an IC50 <6.25; 53.69 ± 3.24 and 147.1 ± 1.48 μg/mL, respectively. In the anti-H. pylori in vitro, HETa did not show MIC at the concentrations tested, but it reduced the turbidity of H. pylori plaques by 22%. The results showed that HETa is not cytotoxic in vitro to CHO-K1 and AGS cells, but in in vitro genotoxicity assays, it resulted in the induction of varying responses depending on the concentration and experimental condition, may be some genotoxic, or sometimes prevent or reverse the induced genotoxicity. In the in vivo toxicity models, HETa was shown to be relatively safe after acute administration in mice; and subchronic in rats (NOAEL of 800 mg/kg/day); and therefore, HETa has a good safety margin for therapeutic use. The results of antiulcerogenic and antisecretory activity of HETa are possibly related to the presence of antioxidant phenolic compounds, and seem to support, in a certain way, its popular use.